Manejo agronómico del cultivo de pimiento (Capsicum annuum L.) en el Ecuador - SUAREZ CRUZ, PEDRO LUIS (2023)
The current information was made with the purpose of contributing in a certain way, to the various producers and farmers who are directly involved with the cultivation of pepper. Supplying effective and efficient information on the correct agronomic management of the pepper crop (Capsicum annuum L.) in Ecuador. Agriculture leaves positive balances in terms of economic terms, bringing good economic items into the country, therefore, it is of great importance that the farmer has an idea of the various demands that the crop requires during all its physiological stages, since the good Management of this allows to increase production and thus optimize the profitability of the crop. The success will depend directly on the management that is granted, that is, to fully comply with the tasks and demands of the crop, since, if it is managed incorrectly, we could go through multiple adversities, which would trigger, in a reduction in terms of to production and therefore destabilizing the economy of farmers. It is worth mentioning that in our country, Ecuador, the climatic conditions favor the optimal development and growth of the pepper crop, for such reasons, it must be improved in the technical part so that it affects its production, to have a better profitability and for Therefore, a greater and better exploitation of the crop so that it continues to innovate and many farmers may be interested in carrying it out, gaining more hectare planted and with it, having a greater production of the pepper crop.